2021
DOI: 10.1016/j.eclinm.2021.100945
|View full text |Cite
|
Sign up to set email alerts
|

Estimated impact of maternal vaccination on global paediatric influenza-related in-hospital mortality: A retrospective case series

Abstract: Background: Influenza virus infection is an important cause of under-five mortality. Maternal vaccination protects children younger than 3 months of age from influenza infection. However, it is unknown to what extent paediatric influenza-related mortality may be prevented by a maternal vaccine since global age-stratified mortality data are lacking. Methods: We invited clinicians and researchers to share clinical and demographic characteristics from children younger than 5 years who died with laboratory-confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…A recent prospective cohort research also revealed that pregnant women who were infected with in uenza during pregnancy were more likely to have adverse pregnancy outcomes, such as late pregnancy loss and a reduction in their infants' birthweight when compared to women who were not infected [7,[9][10][11][12]. Additionally, acute lower respiratory infection (ALRI) caused by the in uenza virus is a leading cause of death in children under the age of ve [13,14]. In 2018, in uenza was linked to 15,300 in-hospital deaths in children under the age of ve worldwide [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent prospective cohort research also revealed that pregnant women who were infected with in uenza during pregnancy were more likely to have adverse pregnancy outcomes, such as late pregnancy loss and a reduction in their infants' birthweight when compared to women who were not infected [7,[9][10][11][12]. Additionally, acute lower respiratory infection (ALRI) caused by the in uenza virus is a leading cause of death in children under the age of ve [13,14]. In 2018, in uenza was linked to 15,300 in-hospital deaths in children under the age of ve worldwide [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, acute lower respiratory infection (ALRI) caused by the in uenza virus is a leading cause of death in children under the age of ve [13,14]. In 2018, in uenza was linked to 15,300 in-hospital deaths in children under the age of ve worldwide [13,14]. More than a third of in-hospital deaths were in children under the age of six months, with the majority (82%) occurring in low-income and lower-middle-income nations (LMICs).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations